Effects of low molecular weight galactomannans based standardized fenugreek seed extract in subjects with high fat mass: A randomized, double-blind, placebo-controlled clinical study - Pallavi Onkar Deshpande, Vivek Bele, Kedar Joshi, Prasad Arvind Thakurdesai (Journal of Applied Pharmaceutical Science, 2020)
The present investigation evaluated the effects of low molecular weight galactomannans-based standardized fenugreek seeds extract (LMWGAL-TF) on human subjects with high-fat mass for 8-weeks using a prospective, randomized, double-blind, placebo-controlled design. Twenty-four subjects with percent body fat were randomized to ingest a capsule of LMWGAL-TF (500 mg, once a day) or the matching placebo at a 1:1 ratio for 8 weeks. The outcome measurements were recorded at baseline, week-4, and week-8 (end of the treatment). The efficacy outcome included fat mass (absolute, non-fat mass and %) by skinfold thickness method (along with triceps, suprailiac, and abdominal) and bioelectrical impedance analysis method, body weight, body mass index, and abdominal girth. The standard safety parameters were measured, such as adverse events, vital signs, hematology, and biochemistry. Eight weeks of LMWGAL-TF supplementation showed significant reduction in suprailiac skinfold thickness (v/s baseline) and abdominal skinfold thickness (v/s baseline and v/s placebo), and percent fat mass, (v/s baseline). The LMWGAL-TF supplementation was found to be safe and well-tolerated. In conclusion, LMWGAL-TF supplementation showed safety and efficacy in reducing skinfold thickness (abdominal and suprailiac) and percent body fat in subjects with a high fat mass.
Keywords: Fenugreek seed, low molecular weight galactomannans, fat mass, skinfold thickness, obesity.